2013
DOI: 10.1007/s11661-013-1911-8
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Growth Morphologies in Al-Zn Alloys—Part II: Phase-Field Computations

Abstract: In Part I of this article, the role of the Zn content in the development of solidification microstructures in Al-Zn alloys was investigated experimentally using X-ray tomographic microscopy. The transition region between h100i dendrites found at low Zn content and h110i dendrites found at high Zn content was characterized by textured seaweed-type structures. This Dendrite Orientation Transition (DOT) was explained by the effect of the Zn content on the weak anisotropy of the solid-liquid interfacial energy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
50
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 28 publications
5
50
0
Order By: Relevance
“…Prior studies have observed seaweed-like structures during solidification either at near-isothermal conditions [24][25][26][27] or in deeply undercooled metallic melts. [28][29][30] Textured seaweed structures were also observed by Rappaz et al [8][9][10]19] in aluminum alloys when zinc was added at compositions of 25 to 55 wt pct. Our results in Mg-Zn, combined with those of Rappaz et al in Al-Zn, support Rappaz's hypothesis that the increase in interfacial energy anisotropy due to the addition of Zn alters the growth morphology.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…Prior studies have observed seaweed-like structures during solidification either at near-isothermal conditions [24][25][26][27] or in deeply undercooled metallic melts. [28][29][30] Textured seaweed structures were also observed by Rappaz et al [8][9][10]19] in aluminum alloys when zinc was added at compositions of 25 to 55 wt pct. Our results in Mg-Zn, combined with those of Rappaz et al in Al-Zn, support Rappaz's hypothesis that the increase in interfacial energy anisotropy due to the addition of Zn alters the growth morphology.…”
supporting
confidence: 62%
“…In contrast, the anisotropy in hcp zinc is very large, as high as 30 pct between the c-direction and the growth directions in the basal plane. [9,10] Based on this, Rappaz et al hypothesized that the addition of Zn increased the anisotropy causing a dendrite orientation transition [8][9][10]19] in Al alloys. In terms of the influence of imposed thermal conditions, Pettersen et al [16,17] demonstrated that the growth direction of primary a-Mg dendrites in a directionally solidified (DS) AZ91 alloy (90.8Mg-8.25Al-0.7Zn-0.35Mn, wt pct) could be altered from h1120i at low G and high V to h2245i for high G and low V. In addition, the number of secondary arm side branches transformed from the expected six to only three.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…al. [24] in directionally solidified Al-Zn alloys, in which they observe an extended transition between <100> growth and <110> growth with increasing Zn content. In the intermediate range, referred to as the 'Dendrite Orientation Transition, (DOT)', they find that competition between the differently directed growth anisotropies give rise to textured, seaweed-like structures.…”
Section: Further Discussionmentioning
confidence: 99%
“…Microstructure selection maps (in undercooling-anisotropy space) produced by Brener et al [31] using solvability theory indicate a range of such transitions should occur, while simulations by Haxhimali et al [32] have suggested that many common metals may lay close to the dendritic-"seaweed" transition. One such transition has been observed directly as a function of composition in Al-Zn alloys by Dantzig et al [33]. A range of undercooling mediated growth direction transitions have also been observed by Castle et al [34] in Cu-10at.% Ni alloy, in which 4-, 6-and 8-fold symmetric dendrites are observed as the undercooling is progressively increased, with 4-fold symmetry finally being recovered at the highest undercoolings achieved, providing strong evidence for velocity mediated transitions in the growth direction.…”
Section: Introductionmentioning
confidence: 86%